The Cognitive Reflection Test and Numeracy as a Predictor of Students' Choice of Major in Undergraduate Programs - Mostafa Deldoost; Parviz Mohammadzadeh; Mohammad Taghi Saeedi; Akram Akbari (LED Edizioni Universitarie, 2019)
Currently, choosing a field of study is one of the most important decisions people make. In this regard, the existence of individual differences can affect the decision-making process, as several studies have shown the influence of cognitive bias on how indi viduals make decisions and employ the process of judgment, which depend on their cognitive abilities. The purpose of this study is to examine the predictive features of the Cognitive Reflection Test and numeracy skills for the probability of choosing a field of study for first-year college students at University of Tabriz. For this purpose, by using a simple random sampling method, a number of 117 freshmen from the faculties of Medicine, Engineering, Humanities, and Economics at the University of Tabriz were selected, and two cognitive reflection and numeracy tests were conducted with them. The results of the regression analysis showed that higher CRT and numeracy have a positive and significant effect on choosing a field in engineering and pharmacy faculties.